Children's and YA books in the college classroom : essays on instructional methods - Dial-Driver, Emily; Ford, Jim, 1972-; Beam, Sara N., 1980- (Jefferson, North Carolina : McFarland & Company, Inc., Publishers, 2015)
"Using children's and young adult literature can improve a variety of college classes in fields as varied as biology, computer game development, political science and history. The contributors describe innovative teaching strategies using dystopian fiction, graphic narratives, fairy tales and mythology. Children's literature can support student learning by raising levels of academic rigor, creativity and critical thinking"--
Preface / Emily Dial-Driver -- Introduction / Jim Ford -- Part I. Inside the English classroom. Out of the sandbox / Emily Dial-Driver -- In appreciation of mere "horseflesh" / Sara N. Beam -- Magical persuasion / Scott Reed and Frances E. Morris -- Once upon a time / Nataliya Romenesko -- Making a case / Robin M. Murphy and Macy McDonald -- Graphic language (devices) in the high school classroom / Jesse Stallings -- Steppin' out with "jabberwocky" / Mike Turvey -- Composing a work that no one hero could compose alone / Sara N. Beam and Holy Clay-Buck -- The truth about native stories / Sally Emmons -- Part II. Beyond the English classroom. Shifting perspectives / Hugh Foley -- The story, myth, legend of jumping mouse / David Newcomb -- happy hedgehogs, happy students / Gioia Kerlin -- Unwinding ethical questions / Jacqueline Bach, Melanie Hundley and Emily Tarver -- Children's books from serious, adult comcepts / Laura Gray and Gary Moeller -- Image and text in The tale of Peter Rabbit / Michael McKeon -- Trees, not poles / Peter Macpherson -- Freedom / Carolyn Taylor -- Thinking about the unthinkable / Paul B. Hatley -- Biology tales / D. Sue Katz Amburn -- Biblical studies through Yertle, Aslan and Little red riding hood / Gregory Stevenson -- Timber!!! / Francis A. Grabowski III -- Growling bears / Weldon Lee Williams and David Blakely -- Girls and boys stay in with media / Juliet Evusa -- Part III. Student perspectives. The whole picture / Erika Carter -- Sources of morality / Kimberly Qualls -- My lady hero / H.J. Bates -- Tulsa's coming-of-age stories / Jessica Limke -- Into the swamp / Davey Rumsey -- Epilogue / Sara N. Beam.
Includes bibliographical references and index.
Keywords: Children's literature -- Study and teaching (Higher); Young adult literature -- Study and teaching